2011
DOI: 10.4103/1735-3327.86041
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between cone beam computed tomography and panoramic radiography in the assessment of the relationship between the mandibular canal and impacted class C mandibular third molars

Abstract: Background:Preoperative radiographic evaluation of impacted third molars is essential to determine the proximity to the mandibular canal to minimize the risk of nerve injury. Our study aim was to evaluate the relationship between the mandibular canal and impacted mandibular third molars using cone beam computed tomography (CBCT) and to compare findings therein with panoramic radiographic signs.Methods:CBCT images were taken from 29 patients having 43 Class C impacted mandibular third molars whose panoramic rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…By moving towards the anterior area, the canal gets farther away from posterior teeth apex, so that, the average distance of mesial root of the first molar on the left and right sides was, 3.96 to 4.64 mm, respectively. Fewer studies were performed to examine the distance of the third molars roots from MC, and most studies in this field only tried to examine the canal course in the impacted and unerupted third molar area (19,20). Chong et al on 272 second mandibular molars, reported that in 55% of cases, the distance between the root apex and inferior alveolar nerve was less and equal to 3 mm, which is close to the results of this study (21).…”
Section: Discussionsupporting
confidence: 86%
“…By moving towards the anterior area, the canal gets farther away from posterior teeth apex, so that, the average distance of mesial root of the first molar on the left and right sides was, 3.96 to 4.64 mm, respectively. Fewer studies were performed to examine the distance of the third molars roots from MC, and most studies in this field only tried to examine the canal course in the impacted and unerupted third molar area (19,20). Chong et al on 272 second mandibular molars, reported that in 55% of cases, the distance between the root apex and inferior alveolar nerve was less and equal to 3 mm, which is close to the results of this study (21).…”
Section: Discussionsupporting
confidence: 86%
“…In some studies, it was found that interruption of the radiopaque borders of the canal in PAN images predicted a direct contact between the roots of the third molar and the mandibular canal observed in CBCT 45,49-52 ( Figure 1), and in other studies, it was found that darkening of the roots in PAN images predicted a direct contact between the roots of the third molar and the mandibular canal observed in CBCT. 48,50,52,53 In one of the studies darkening of the roots was present in 5 of 43 of the PAN images, and the absence of cortication between the third molar and the mandibular canal was present in 33 of 43 of CBCT images. 48 The 5 cases were interpreted with no bony separation in the CBCT images, on the other hand, 28 cases were also determined with no bony separation in the CBCT images, and therefore, the agreement between the presence of darkening of the roots in the PAN images and the absence of bone between the tooth and the mandibular canal was only 15.2%.…”
Section: Level 2-effect On Diagnostic Accuracymentioning
confidence: 99%
“…48,50,52,53 In one of the studies darkening of the roots was present in 5 of 43 of the PAN images, and the absence of cortication between the third molar and the mandibular canal was present in 33 of 43 of CBCT images. 48 The 5 cases were interpreted with no bony separation in the CBCT images, on the other hand, 28 cases were also determined with no bony separation in the CBCT images, and therefore, the agreement between the presence of darkening of the roots in the PAN images and the absence of bone between the tooth and the mandibular canal was only 15.2%. 48 Recently, in one study, it was found that if interruption of the radiopaque borders of the canal and/or diversion of the canal and/or narrowing of the lumen of the canal was present in the PAN images, there was 1.6 times the probability that a direct contact was seen in the CBCT.…”
Section: Level 2-effect On Diagnostic Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some high‐risk cases could require the use of 3‐D cone beam computed tomography (CBCT). Although CBCT can be associated with a greater financial and biologic cost to a patient than a panoramic radiograph, it is widely accepted that the increase in preoperative information makes this a superior imaging modality in surgical treatment planning for the extraction of impacted third molars …”
Section: Introductionmentioning
confidence: 99%